RANCANG BANGUN SISTEM INFORMASI SUPLAI MATERIAL BERBASIS WEB - Dera Susilawati; M. Ridwan Arif Cahyono; Nabila Putriardyana Cinta (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2026)
This research aims to design and develop a web-based material supply information system to address delays in material delivery at the PPC Plant D Department of PT PCR. The previous system relied on Microsoft Excel with macros, which was considered inefficient due to its lack of real-time data updates. The new system was developed using PHP Native with a MySQL database and tested using the blackbox method. The results showed that the system could automatically display real-time material delivery data through features such as auto-refresh, auto- scroll, and search functionality. Additionally, the responsive interface allows for easier monitoring of delivery schedules between production departments. The implementation of this web-based system has proven to increase efficiency and effectiveness in material delivery to the Building process, reducing the average delay caused by material factors from 6.276% to 2.27%. Therefore, the web-based information system effectively improves the distribution process of materials in a manufacturing environment.